COMPARATIVE ANALYSIS OF SYNTAX IN ENGLISH AND UZBEK (Ustozlar uchun, 2026)
This study provides a comparative analysis of syntactic structures in English and Uzbek, focusing on word order, sentence types, grammatical relations, and functional aspects of syntax. The research highlights both universal and language-specific features, demonstrating how typological differences (analytic vs. agglutinative structures) influence sentence formation. The findings contribute to contrastive linguistics, translation studies, and language teaching methodology.